De novo KCNK4 variant caused epilepsy with febrile seizures plus, neurodevelopmental abnormalities, and hypertrichosis - Yan, Hong-Jun; Liu, Wen-Hui; Xu, Min-Xing; Wang, Peng-Yu; Gu, Yu-Jie; Li, Hua; Guo, Jing; Luo, Sheng (Frontiers in Genetics, 2025)
BackgroundEpilepsy with febrile seizures plus (EFS+) is a syndrome with a strong genetic component. Previously, variants in several genes encoding ion channels have been associated with EFS+. However, the etiology in the majority of patients remains undetermined.MethodsTrio-based whole-exome sequencing was performed on a patient with EFS+. Previously reported KCNK4 variants were systemically reviewed to analyze the phenotypic spectrum and core phenotypes.ResultsA novel de novo KCNK4 variant (c.415G>A/p.Gly139Arg) was identified in a patient with EFS+, neurodevelopmental abnormalities, and hypertrichosis. The identified variant was absent in normal populations, indicated to alter hydrogen bonds with surrounding residues by various protein modeling, predicted to be damaging for protein function by twenty algorithms, located in residues of high conservation across species, and classified as pathogenic by the ACMG guidelines. Protein modeling analyses of the variant suggested a possible gain-of-function effect. Analysis of other eight cases with KCNK4 variants outlined the phenotypic spectrums of KCNK4, ranging from mild benign epilepsy, EFS+ with neurodevelopmental abnormalities, to syndromic neurodevelopmental disorders and revealed neurodevelopmental abnormalities and epilepsy as its core phenotypes. Integrated analysis suggested that minor allele frequency and in silico meta-predictors effectively distinguish pathogenic variants.ConclusionThis study suggested the KCNK4 gene as a novel candidate causative gene of EFS+, which would be helpful for the genetic diagnosis and clinical management of patients.